An effective colour feature extraction method using evolutionary computation for face recognition. (1st January 2011) - Shih, Peichung; Liu, Chengjun
This paper presents a colour feature extraction method using a Genetic Algorithm (GA) to seek the optimal colour space transformation that leads to an effective image representation for face recognition. A new colour space, LC1C2, consisting of one luminance (L) channel and two chrominance channels (C1, C2) is introduced as a linear transformation of the input RGB colour space. The specific transformation from the RGB colour space to the LC1C2 colour space is optimised by a GA where a fitness function guides the evolution towards higher recognition accuracy.